PERAN DAN KEDUDUKAN PETANI DALAM SISTEM PERDAGANGAN INTERNASIONAL - Imanullah, Moch Najib; Latifah, Emmy; Adiastuti, Anugrah (Yustisia, 2016)
AbstractThis study aims to determine the role and position of farmer in the international trading system today. The development of the international trading system has an impact on the shift of food production system and food security policy which ultimately also has an impact on farmer’s role and position in the global market. Evolution of agricultural structures in any periodization provide a clear description of the role and position of farmers in every era to enter the globalization. The globalization era was shaping a more liberal market system so that the role and position of farmers is becoming increasingly difficult in the international trading system. AbstrakPenelitian ini bertujuan untuk mengetahui peran dan kedudukan petani dalam sistem perdagangan internasional dewasa ini. Perkembangan sistem perdagangan internasional berdampak pada pergeseran sistem produksi pangan dan kebijakan ketahanan pangan yang akhirnya juga berdampak pada peran dan kedudukan petani di pasar global. Evolusi struktur pertanian dalam setiap periodesasi memberikan gambaran yang jelas mengenai peran dan kedudukan petani pada setiap masanya hingga memasuki era globalisasi. Era globalisasi membentuk sistem pasar yang lebih liberal sehingga peran dan kedudukan petani menjadi semakin sulit dalam sistem perdagangan internasional.